2020
DOI: 10.1088/1361-648x/abc4c9
|View full text |Cite
|
Sign up to set email alerts
|

Aggregation of methacrylate-based ternary biomimetic antimicrobial polymers in solution

Abstract: Using detailed atomistic simulations, we explore the morphological characteristics of aggregates formed in solution phase by ternary biomimetic antimicrobial (AM) methacrylate polymers, composed of hydrophobic, charged cationic and polar functional groups and compare it with aggregate morphologies of binary methacrylate polymers, composed only of hydrophobic and charged cationic functional groups. The effect of sequence of the constituent functional groups on aggregate conformation is also studied by consideri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 57 publications
2
18
0
Order By: Relevance
“…Inspired by these studies, our group has recently conducted a systemic investigation of the effect of hydrophilic groups on antibacterial activity and biocompatibility of statistical amphiphilic ternary polymers. [ 107 ] In agreement with the previous finding of Rani [ 115,116 ] and others, [ 109 ] we found that unlike hydrophobic groups that directly disrupt the cell membrane hydrophilic groups have an indirect but important impact on bioactivity through tuning of the hydrophobic/hydrophilic balance and global hydrophobicity, leading to a change in the aqueous characteristics of polymers. Therefore, in antimicrobial polymer design, an appropriate hydrophobic/hydrophilic balance as well as the structural features of the hydrophilic group, such as length, flexibility, and hydrophilicity of the hydrophilic chain, are key determinants that can be optimized to enhance the AMP selectivity toward pathogens over host cells.…”
Section: Design Principles Of Polymers Structure–activity Relationshi...supporting
confidence: 92%
“…Inspired by these studies, our group has recently conducted a systemic investigation of the effect of hydrophilic groups on antibacterial activity and biocompatibility of statistical amphiphilic ternary polymers. [ 107 ] In agreement with the previous finding of Rani [ 115,116 ] and others, [ 109 ] we found that unlike hydrophobic groups that directly disrupt the cell membrane hydrophilic groups have an indirect but important impact on bioactivity through tuning of the hydrophobic/hydrophilic balance and global hydrophobicity, leading to a change in the aqueous characteristics of polymers. Therefore, in antimicrobial polymer design, an appropriate hydrophobic/hydrophilic balance as well as the structural features of the hydrophilic group, such as length, flexibility, and hydrophilicity of the hydrophilic chain, are key determinants that can be optimized to enhance the AMP selectivity toward pathogens over host cells.…”
Section: Design Principles Of Polymers Structure–activity Relationshi...supporting
confidence: 92%
“…Both ternary and binary polymers have a degree of polymerisation (DP) = 19 with the groups in a random sequence with a composition of 6 AEMA units, 8 EMA units, 5 HEMA units for model T polymers and 6 AEMA units, 13 EMA units for model B polymers. For further details and an in depth study of such polymers and their conformations in solution and membrane phase we refer to our previous works [17, 18]. The bacterial membrane consists of 38 POPG and 90 POPE lipid molecules per leaflet to mimic the inner membrane of the Gram negative bacteria [29].…”
Section: Models and Methodsmentioning
confidence: 99%
“…The AEMA units, 13 EMA units for model B polymers. For further details and an in depth study of such polymers and their conformations in solution and membrane phase we refer to our previous works [17,18]. The bacterial membrane consists of 38 POPG and 90 POPE lipid molecules per leaflet to mimic the inner mem-module [30] was used to construct the the membrane system, similar to our previous works [31,32,18].…”
Section: Models and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to understand how differently they interact with bacterial membranes when compared to the previously described binary composition in designing better antimicrobial mimics. Recently we showed that replacing some of the hydrophobic groups in a binary biomimetic polymer with polar groups significantly alters how the resultant ternary polymers interact in solution phase and with bacterial membranes. , The studies also strongly suggest that the inclusion of polar groups smears the overall hydrophobicity of such polymers and result in a globular conformations when partitioned into the bacterial membrane, likely mimic of defensin-like antimicrobial peptides. , …”
Section: Introductionmentioning
confidence: 99%